Micromegas with high-granularity readout: stability and performance at high particle rates. Issue 1 (1st November 2022) - Franchellucci, S.; Alviggi, M.; Camerlingo, M. T.; Canale, V.; Pietra, M. Della; Di Donato, C.; Di Nardo, R.; Iengo, P.; Iodice, M.; Petrucci, F.; Sekhniaidze, G.
Abstract : The new generation of particle physics experiments at current and future colliders demands more and more robust detectors. A proposed solution to the stringent requirements are the Small-pad Resistive Micormegas. This technology is being developed during recent years, in the framework of the new R&D project RHUM. Different resistive schemes have been implemented. The different behaviours of the embedded resistor layout and the Diamond-Like Carbon (DLC) uniform layers scheme have been studied. Results at very high rate are shown. HV stability studies with two different gases are reported.